Consistents of car’s parking in Lithuanian towns - Burinskienė, Marija; Paliulis, Gražvydas (Transport, 2003)
Large towns of Lithuania should especially focus on the solution of the parked cars; and modem technologies should be employed for that. The research methods have been substantiated and the recommendations for the technical regulations of the short-term and long-term car parking near different objects of attraction have been worked out on the basis of selective natural research, which is significant when issuing technical specifications to investors on the way the surroundings of the objects being built should be arranged and on what rearrangement of the urban streets is necessary. With a high level of motorization, the organization of the car parking process is a complicated problem of urban planning. The accumulated experience and the carried out analysis show that car parking problems can be positively solved even with a high level of motorization by: making use of the urban area as reasonably as possible so that the spaces could take the greatest possible number of cars; limiting the duration of parking so that the greater number of cars could use the same parking space; promoting car sharing; differentiating the entrance possibilities for different vehicles with regard of time, space and fee size. Solutions related to the determination of the parking space should be achieved in the context of the strategy of total urban development, area and traffic planning, traffic safety improvement and preservation of unique environment. First Published Online: 19 Dec 2011